Problems of treatment adherence in patients with rheumatoid arthritis and comorbidity - N. M. Nikitina; E. V. Egorova; I. F. Melehina; S. N. Grigoryeva; A. P. Rebrov (Архивъ внутренней медицины, 2020)
Aim of the study. Evaluation of treatment adherence in patients with rheumatoid arthritis (RA) and comorbidity.Materials and methods. One hundred thirty-two women (mean age: 55.5 ± 10.5 years) with proven RA (mean duration of disease: 10.2 [4; 14] years) were included in this study. Patients with moderate and high disease activity were prevalent (average DAS28: 5.0 [4.3; 5.8]). All patients had comorbidities. All patients underwent clinical examination, laboratory evaluation and imaging. Functional capacity was assessed using the Steinbroker classification (functional class — FC) and Stanford Health Assessment Questionnaire (HAQ). Pain severity was evaluated using visual analog scale (VAS). Patients’ social status was assessed. Baseline adherence to treatment was evaluated using two questionnaires. Morisky-Green questionnaire was used to evaluate general adherence to treatment among 132 (100%) patients. Quantitative evaluation of treatment adherence was performed in 82 (62.1%) patients using N.A. Nikolaev questionnaire.Results. Analysis of adherence to treatment as assessed by Morisky-Green questionnaire has established that 68 (52.3%) of patients are non-adherent to treatment. Low treatment adherence as assessed by Nikolaev questionnaire was found in 33 (40.3%) of patients. Lifestyle modification was characterized by lowest adherence. Young age, lower duration of disease and lower income were predictive of higher adherence to treatment. Non-adherent patients had higher RA activity index and lower functional capacity.Conclusion. Simultaneous use of several methods to assess treatment adherence is a reasonable way to get more information about the patient and to implement therapy as planned. Evaluation of baseline adherence to treatment among patients with rheumatoid arthritis allows to develop an optimal plan for follow-up and treatment control.